2015
DOI: 10.2527/jas.2014-8824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ractopamine and arginine dietary supplementation for sows on growth performance and carcass quality of their progenies1

Abstract: The objective of this study was to evaluate the effects of ractopamine (Rac) and Arg fed to pregnant sows from d 25 to 53 of gestation on fetal muscle development as well as the performance and carcass characteristics of the progeny. One hundred sows were divided into 4 treatments including a control diet, the control plus 1% Arg, the control plus 20 mg/kg Rac, and the control diet supplemented with both additives at the same levels as those used separately. During the farrowing process the data evaluated were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 45 publications
7
18
1
4
Order By: Relevance
“…However, interestingly and in contrast to the present study, a lower TNF was observed in offspring from supplemented compared with unsupplemented sows. One explanation for the discrepancy between the observation in our study and the study of Garbossa et al [40] could be the mode of l -arginine supplementation, either during d 14-28 or 25-53 of gestation, respectively, and at either 0.89% or 1.00% of the diet, respectively. With these combined results in mind, it is relevant to reflect on the extent to which supplementary l -arginine is directing dietary energy for hyperplasia or hypertrophy in fetuses during the different phases of gestation.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, interestingly and in contrast to the present study, a lower TNF was observed in offspring from supplemented compared with unsupplemented sows. One explanation for the discrepancy between the observation in our study and the study of Garbossa et al [40] could be the mode of l -arginine supplementation, either during d 14-28 or 25-53 of gestation, respectively, and at either 0.89% or 1.00% of the diet, respectively. With these combined results in mind, it is relevant to reflect on the extent to which supplementary l -arginine is directing dietary energy for hyperplasia or hypertrophy in fetuses during the different phases of gestation.…”
Section: Resultscontrasting
confidence: 99%
“…This finding contradicts our hypothesis that underprivileged fetuses would preferentially benefit from ARG supplementation by an increased placental vascularization. Results of a recent study [40] suggested that supplementing the gestational diet with either l -arginine, ractopamine, or a combination of the two increased myofiber diameter, indicating that supplementation had an effect on muscle fiber hypertrophy rather than hyperplasia. Ultimately, this resulted in a lower proportion of low BtW piglets (< 0.8–1.2 kg BtW), and an increased proportion of medium and high BtW piglets (> 1.2–1.6 kg BtW) from l -arginine supplemented compared with unsupplemented sows [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, amino acids supplementation was given in the third trimester of gestation most of the trials (60%), which could explain the results for litter size. However, despite the differences in methodology, amino acid supplementation has shown positive effects on the variability of piglet birth weight (Athorn, Wilkinson, & Henman, 2017;Dallanora et al, 2017;Garbossa et al, 2015).…”
Section: Ta B L Ementioning
confidence: 99%
“…As fêmeas são muito mais sensíveis à suplementação proteica nessa fase em comparação com outras fases. A demanda de proteína pode ser suprida através de dietas contendo fontes de ingredientes vegetais ou animais e complementada com a adição de aminoácidos industriais (BOYD et al, 2002;PETTIGREW;YANG, 1997 Garbossa et al (2015) observaram que leitões nascidos de matrizes com dietas suplementadas com 20 mg/kg de ractopamina durante 25 a 50 dias de gestação podem apresentar taxas de crescimento mais elevadas, aumentando a deposição muscular da carcaça, melhorando a viabilidade econômica.…”
Section: Lista De Figurasunclassified